Drug-Coated Balloon-Only Angioplasty Outcomes in Diabetic and Nondiabetic Patients with De Novo Small Coronary Vessels Disease - Zia Ur Rahman, Irfan Ali Khan, Qazi Najeeb Ullah Amin, Kashif Ullah Shah, Farman Ullah, Sami Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It is still difficult to use drug-eluting stents for the revascularization of small arteries. For patients with diabetes, treatment with a drug-covered balloon for de novo lesions in small coronary vessels are an appealing restoration option. The cause of this research ends up to evaluate the efficacy of DCB-simplest angioplasty for treating small-vessel sickness. Place of study and duration: Conducted at Cardiology department of Hayatabad Medical Complex Peshawar for the duration from Feb 2019 to Feb 2022. Methods: A fashionable of 1198 patients with small vascular illness treated with DCB-best approach were observed at Hayatabad Medical Complex Peshawar from Feb 2019 to Feb 2022. Patients were classified as each having diabetes or now not having diabetes. Clinical and angiographical follow-up were organise at 12 months. Target lesion failure and non-primary good sized damaging cardiac activities were used as primary outcomes. Results: Diabetic patients had a greater hazard of intention lesion failure (17.9% vs. 11.4%, P=0.006), and the charge of intention lesion revascularization (9.2% vs. 4.5%, P=0.014) emerge as moreover considerably unique many of the 2 companies even as analysed independently. Adjusting for exclusive factors did now not reduce the significance of diabetes mellitus as a predictor of every TLF (HR: 2.712, CI: 1.254-5.864, P=0.011) and intention lesion revascularization (HR: 3.698, CI: 1.112-12.298, P=0.033). However, there had been no vast versions amongst companies for MACE (19% vs. 2.7%, P=0.120) or for intention vessel myocardial infarction (0.6% vs. 0.1%, P=0.110). Conclusion: Reductions in TLF and MACE fees had been seen with drug-coated balloon treatment alone. At three hundred and sixty-five days after treatment with DCBs, diabetes is an independent predictor of intention lesion failure and intention lesion revascularization in small coronary arteries. Within a year, we observed no essential variations in MACE some of the corporations.